Adaptive Social Protection: A Systematic Literature Review and Research Agenda - Prihantika, Ita; Panca Rahmadhani, Tia; Mulyana, Nana (Policy & Governance Review, 2024)
Adaptive social protection represents a novel form of approach that is more holistic in addressing issues related to disasters associated with climate change and social shifts. Adaptive social protection has resurfaced social protection as a new approach to assist an individual or society to mitigate vulnerability or potential harms related to poverty and climate change. Despite the necessity for enhanced comprehension of adaptive social protection approaches, there exists a dearth of scholarly research on this subject. This study strives to address this gap. Therefore, the primary objective of this research is to map the gaps in studies related to the topic of adaptive social protection, thereby enabling us to identify future research agendas. Through this article, we systematically review existing studies in social adaptive protection within two decades. 305 articles are categorized and analyzed using the SPAR-4-SLR protocol by Paul (2021) and employs the VosViewer 16.1.19 to scrutinize and dissect this topic in a bibliometric approach and map the distribution on authorship, countries, institutes, and keywords. We found that the existing publications in adaptive social protection primarily originated from the United States, United Kingdom, and Canada. By synthetically analyzing the keywords, the dominant hot spot of adaptive social protection research could be concluded as "adaptive management", "climate change", or "adaptation".